2006
DOI: 10.1021/ef060140f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Anisotropic Behavior of Wood Char Particles during Gasification

Abstract: Wood is a strongly anisotropic material, and likewise, the char produced by pyrolysis of wood is characterized by a strong anisotropy. This anisotropic behavior allows relatively easy transport of gas in the longitudinal (L) direction of the wood, but the transport is much less easy in the radial (R) and tangential (T) directions. Despite this, this property has normally not been included in mathematical model descriptions of gasification of thermally thick particles. The present paper describes a study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Groeneveld and van Swaaij (1980) compared flake and spherical particles during gasification and concluded that at constant particle volume, spherical particles were less reactive. A few other authors conducted experiments to determine the influence of particle shape on gasification (Henriksen et al, 2006;Moilanen et al, 1993;De Diego et al, 2002). Henriksen et al (2006) investigated the behavior of parallelepiped pieces of wood and revealed the influence of the dimensions on the rate of conversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groeneveld and van Swaaij (1980) compared flake and spherical particles during gasification and concluded that at constant particle volume, spherical particles were less reactive. A few other authors conducted experiments to determine the influence of particle shape on gasification (Henriksen et al, 2006;Moilanen et al, 1993;De Diego et al, 2002). Henriksen et al (2006) investigated the behavior of parallelepiped pieces of wood and revealed the influence of the dimensions on the rate of conversion.…”
Section: Introductionmentioning
confidence: 99%
“…A few other authors conducted experiments to determine the influence of particle shape on gasification (Henriksen et al, 2006;Moilanen et al, 1993;De Diego et al, 2002). Henriksen et al (2006) investigated the behavior of parallelepiped pieces of wood and revealed the influence of the dimensions on the rate of conversion. Experimentally, he showed that char reactivity was considerably higher when the particle was positioned so that the fibers were in the direction of the reactant gas flow.…”
Section: Introductionmentioning
confidence: 99%
“…The chars were kept for 1 h at the final temperature, cooled under nitrogen and stored afterwards in a sealed container. The low heating rate is expected to ensure good temperature uniformity in the wood particle and to lead to a quite homogeneous wood char, from the structural and chemical viewpoints, as demonstrated by [24] and pointed out by [25] and [26]. During the pyrolysis reaction, the char par ticles shrink and get an ovoid form.…”
Section: Low Heating Rate Char Preparationmentioning
confidence: 99%
“…Further, the coefficient of moisture diffusion as a function of temperature and moisture content was determined. The anisotropy of effective diffusion, permeability and thermal conductivity of moisture in different directions was determined as well [18,19]. The experiments were carried out under atmospheric pressure at different temperatures (463-483 K).…”
Section: Introductionmentioning
confidence: 99%